2012
DOI: 10.1136/jramc-158-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Fractures in Current Military Deployments

Abstract: Injuries to the spine caused by explosive devices account for greater numbers, greater associated morbidity and increasing complexity than other means of spinal injury managed in contemporary warfare. With the predominance of explosive injury in current conflict, this work provides the first detail of an evolving injury mechanism with implications for injury mitigation research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Basic research is evaluating the behavior of ligaments and vertebral bodies at high strain rates similar to those seen in blast [ 4 , 5 , 10 ]. These can be correlated with work on the injury patterns seen in blast to attempt to derive the posture of the spine at the moment of failure and to postulate the mechanism of failure [ 7 , 12 , 22 ]. For example, Lehman et al [ 15 ] suggest that in underbody blast, the use of body armor by soldiers reduces the mobility of the upper lumbar spine and increases the risk of low lumbar burst fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research is evaluating the behavior of ligaments and vertebral bodies at high strain rates similar to those seen in blast [ 4 , 5 , 10 ]. These can be correlated with work on the injury patterns seen in blast to attempt to derive the posture of the spine at the moment of failure and to postulate the mechanism of failure [ 7 , 12 , 22 ]. For example, Lehman et al [ 15 ] suggest that in underbody blast, the use of body armor by soldiers reduces the mobility of the upper lumbar spine and increases the risk of low lumbar burst fractures.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred twenty-eight spinal fractures during military deployments of the United Kingdom army between 2005-2009 were collected. 40 Ballistic (79%) and nonballistic mechanisms contribute to vertebral fracture, a high incidence of lumbar spine fractures, which are more likely to be due to explosion than gunshot wounding. The authors concluded that due to the predominance of explosive injury in current conflicts, and the research must be directed to this injury mechanism.…”
Section: War and Combat Injuriesmentioning
confidence: 99%
“…The authors concluded that due to the predominance of explosive injury in current conflicts, and the research must be directed to this injury mechanism. 40 War injuries have also been an interest of some studies. The US army collected 65 cases of explosive device assaults on uparmored vehicles during the Afghanistan and Iraq wars.…”
Section: War and Combat Injuriesmentioning
confidence: 99%